2018
DOI: 10.19080/ctoij.2018.09.555758
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma in childhood: Analysis of a Series of 64 Patients treated with Combined Chemotherapy and Radiotherapy

Abstract: Background:The aim of our study is to investigate the epidemiological, clinical, radiological, therapeutic particularities of the nasopharyngeal carcinoma (NPC) in children, and to determine prognostic factors correlated with outcome and features of a series of 64 cases collected in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…If malignancy was suspected in a neck mass case with hard, firm or rubbery consistency, fixed supraclavicular mass, lymph node larger than 2 cm in diameter, persistent enlargement for more than two weeks, no decrease in size after four to six weeks, absence of inflammation, present of ulceration, failure to respond to antibiotic therapy, or accompanied by a thyroid mass, the patient should be referred to a head and neck surgeon for urgent evaluation and possible biopsy. 11,12 The treatment of pediatric NPC had undergone several changes in the last few decades. Until the early 1990's, patients were mostly treated by irradiation, but then chemotherapy was introduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If malignancy was suspected in a neck mass case with hard, firm or rubbery consistency, fixed supraclavicular mass, lymph node larger than 2 cm in diameter, persistent enlargement for more than two weeks, no decrease in size after four to six weeks, absence of inflammation, present of ulceration, failure to respond to antibiotic therapy, or accompanied by a thyroid mass, the patient should be referred to a head and neck surgeon for urgent evaluation and possible biopsy. 11,12 The treatment of pediatric NPC had undergone several changes in the last few decades. Until the early 1990's, patients were mostly treated by irradiation, but then chemotherapy was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Until the early 1990's, patients were mostly treated by irradiation, but then chemotherapy was introduced. 12 Besides the stage of the disease at the commencement of the therapy, the survival rates for young patients are generally better than in adults. The histological Type III which are more common in children possess a higher degree of radio sensitivity and local radio curability, in addition to their tolerability to radiation better than adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neck mass was the most prevalent impetus to seek treatment, as shown in previous studies. 7,9,19 A study in China reported that neck mass affected up to 40.9% of pediatric patients and cranial nerve involvement in 3% patients. 7 This percentage was lower than in our study (Table 2), but neck mass was the most common symptom.…”
Section: Discussionmentioning
confidence: 99%